Associations of Embeddedness and Posttraumatic Stress Disorder among 9/11 Survivors - Meghan K. Hamwey; Cristina D. Pollari; Sukhminder Osahan; Sascha K. Garrey; Felix M. Ortega; Adrienne Solomon; Robert M. Brackbill (MDPI AG, 2021)
Following exposures to traumatic events on 9/11, survivors have reported heightened levels of posttraumatic stress disorder (PTSD). Multiple factors contribute to both the exacerbation and amelioration of PTSD symptoms, including social integration and support. This cross-sectional study aimed to understand and identify associations of embeddedness and psychosocial risk factors by PTSD status for survivors and first responders of 9/11. Results indicate that those with chronic PTSD had the lowest prevalence of both social and emotional embeddedness and many who reported no PTSD symptoms following 9/11 reported moderate levels of social and emotional embeddedness. Overall, our findings suggest those individuals who reported little to no PTSD also reported the most social/emotional embeddedness; whereas those individuals who report greater or chronic PTSD report the least social/emotional embeddedness. As such, it may be beneficial for clinicians across multiple care disciplines and contexts to consider and address the social lives and needs of those individuals experiencing symptoms of PTSD to ensure their emotional and physical needs are truly being met.